Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/lam.13120
|View full text |Cite
|
Sign up to set email alerts
|

Aporphinoid alkaloids as antimicrobial agents against Yersinia enterocolitica

Abstract: Foodborne diseases have become a health issue worldwide, mainly due to the consumption of contaminated foods that are either raw, improperly heat treated or cross‐contaminated after adequate heat treatment foods. A group of alkaloids extracted from plants were tested to evaluate their antimicrobial effect against different strains of Yersinia enterocolitica and other foodborne bacteria. The results obtained reveal that oliveridine and pachypodanthine inhibited Y. enterocolitica growth, with MIC values of 25 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…These alkaloids were shown to inhibit bacterial growth for up to 96 h of culture. Similar MIC values were obtained for other foodborne pathogenic bacteria (Di Marco et al 2019).…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…These alkaloids were shown to inhibit bacterial growth for up to 96 h of culture. Similar MIC values were obtained for other foodborne pathogenic bacteria (Di Marco et al 2019).…”
Section: Introductionsupporting
confidence: 83%
“…Recently, we investigated the inhibitory activity of pachypodanthine against planktonic growth of several strains of Y. enterocolitica . MIC values obtained varied from 25 to 100 µmol l −1 for different biotypes and other Gram‐negative bacteria (Di Marco et al 2019). Aside from the work by Park et al (2017), we have not found any other published report about aporphinoid alkaloids as inhibitors of biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides removing QS signaling molecules, adding QS inhibitors to interfere QS receptors or inactivate signaling molecules was also applied in biological waste treatment systems (Yates et al, 2002;Teplitski et al, 2011;Kalia, 2013). Many QS inhibitors were found including 3-amino-2-oxazolidinone YXL-13, homoserine lactone-like TGKseries, ε-polysine, aporphinoid alkaloids, cladodionen, gingerol, etc (Al-Shabib et al, 2020;Alibi et al, 2020;Brown et al, 2020;Cheng et al, 2020;Di Marco et al, 2020;Li et al, 2020;Parmar et al, 2020;Qin et al, 2020;Shen et al, 2020;Wang et al, 2020b). Vanillin (4hydroxy-3-methoxybenzaldehyde) was used as the QS inhibitor and decreased the biofilm formation by over 45% on reverse osmosis (RO) membrane (Ponnusamy et al, 2009).…”
Section: Adding Qs Inhibitorsmentioning
confidence: 99%
“…Aporphinoids are an important class of alkaloids widely distributed in the plant kingdom. These natural compounds have been shown to exhibit an important spectrum of pharmacological activities as an antimicrobial, [8] antitumor, [9] and antifungal, [10] among others. Even though, potent cholinesterase inhibition has been reported for members of this alkaloid subgroup little is known on their mode of inhibition [11–13] …”
Section: Introductionmentioning
confidence: 99%